Making Game: An Essay on Hunting, Familiar Things, and the Strangeness of Being Who One Is - Peter L. Atkinson (Cultural Dialectics, 2009)
Making Game is a mixed-genre composition in which the author reflects on the philosophical and ethical implications of hunting wild game. This engaging essay is informed by the author's significant background of scholarly engagement with the phenomenological tradition in modern philosophy.